Asymptotic properties of the estimator of the conditional distribution for associated functional data - Hamri, Mohamed Mehdi; Dib, Abdassamad; Rabhi, Abbes (Właściwości asymptotyczne szacunku rozkładu warunkowego dla powiązanych danych funkcjonalnych, 2022)
The purpose of the paper was to investigate by the kernel method a nonparametric estimate of the conditional density function of a scalar response variable given a random variable taking values in a separable real Hilbert space when the observations are quasi-associated dependent. Under some general conditions, the authors established the pointwise almost complete consistencies with rates of this estimator. The principal aim is the investigate the convergence rate of the proposed estimator.
Econometrics = Ekonometria, 2022, Vol. 26, No. 3, s. 21-34
Keywords: nonparametric estimation; small ball probability; quasi-associated data; estymacja nieparametryczna; prawdopodobieństwo small ball; dane quasi-skojarzone